Meet me On the Joy Zone - Harry Williams::::::::: (Harry William Music Publishers)
Piano and vocal score 5 p. On cover: Official Zone Concessioner's Song, photo of "The Zone" signed B. Smith P.P.I.E. 15' On verso of last leaf is the letter from the fair Director-General notifying Harry Williams of the adoption of the song as the official concessioner's song.